Constitutional Accountability in Contemporary Government Systems: A Study of Institutional Design and Legal Oversight Instruments - Basto Da Silva; Didit Darmawan (Civiliza Publishing, 2026)
This theoretical research examines constitutional accountability mechanisms within modern governance structures through a systematic literature review. Constitutional accountability operates as an integrated system comprising oversight institutions, legal instruments, and sanction enforcement processes. The effectiveness of these mechanisms depends on functional coordination among parliamentary, judicial, and independent oversight bodies, balanced application of preventive, detective, and repressive legal instruments, and timely, certain, proportional sanction enforcement. No universal model fits all legal systems due to variations between common law and civil law traditions alongside local political cultural factors. Vertical accountability through public participation and elections complements horizontal accountability, yet both face disruption from politicized recruitment procedures for oversight institution leadership and temporal gaps between digital information speed and slow legal processes. Decentralization produces new accountability layers that frequently prove weaker than central mechanisms. International oversight mechanisms supply moral pressure without adequate coercive power. Recommendations include procedural reforms strengthening inter institutional coordination, explicit mapping of jurisdictional boundaries to eliminate overlaps, and adopting phased sanction systems combining reputational, financial, and penal consequences proportionate to constitutional violation severity.